Способы выражения отрицания в балтийских и славянских языках (на материале русского и литовского языков) - Казимянец, Елена Генриховна (Baltistica, 1989)
THE WAYS OF EXPRESSING NEGATION IN BALTIC AND SLAVIC LANGUAGES The paper is concerned with negation as the universality of language. The content of the given category is determined, and the two ways of its expression in the Russian and Lithuanian languages are observed: the expression of negation by using formal means and negation having no formal expression. The set of means for expressing negation has been worked out and the classification of hese means is provided.